Media exposure, attitude, anxiety and practices among university students during the COVID-19 pandemic - Kamaruzzaman Abdul Manan; Siti Nor Amalina Ahmad Tajuddin; Roslan Ali; Khairul Azam Bahari; Zeti Azreen Ahmad; Kevin Downing (International Journal of Public Health Science (IJPHS), 2022)
The coronavirus disease 2019 (COVID-19) pandemic, which originated from China, went global within weeks. At the time of writing, almost 300 million people around the world have been infected by this potent and fast-spreading disease, which in many cases has paralysed economies and normal daily activities. University students are among the people that have been badly affected by the pandemic, as the movement control order (MCO) has resulted in university closure. Hence, many students are unable to proceed with their regular studies and have to be extra vigilant in dealing with the pandemic. During the MCO period, they rely heavily on media for guidance and information. This study was conducted to examine media exposure, attitude, anxiety, and practices towards COVID-19 amongst the students of Universiti Pendidikan Sultan Idris (UPSI), Perak, Malaysia. A quantitative research design was used to achieve the research objective. A total of 505 respondents answered an online survey and the findings revealed that respondents were highly dependent on various media for updated information about the pandemic, with the majority of them anxious about their safety. These findings are useful for higher education institutions in developing a better learning environment for students and understand the impact of the pandemic on students.